THE EFFECT OF SUSTAINABILITY REPORTING, INSTITUTIONAL OWNERSHIP, MANAGERIAL OWNERSHIP AND INDEPENDENT BOARD OF COMMISSIONERS REGARDING PROFIT MANAGEMENT IN COMPANIES FOOD AND BEVERAGE SECTOR - Pramaiswari, Made Adinda Anugrah Deva; Saputra, Komang Adi Kurniawan; Juniariani, Ni Made Rai (Jurnal Akuntansi Trisakti, 2026)
Financial reports are a crucial instrument for investors in making long-term investment decisions. However, information asymmetry often leads managers to engage in earnings management practices that can mislead users and harm investors. This phenomenon is particularly relevant in the post-pandemic food and beverage sector (2021-2023), where fluctuations in operating costs increase the risk of earnings manipulation to maintain market reputation. This study aims to analyze the influence of sustainability reporting, institutional ownership, managerial ownership, and independent boards of commissioners on earnings management. The research method used was quantitative with a purposive sampling technique, resulting in a sample of 26 food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The data were analyzed using multiple linear regression to examine the relationships between the variables. The results indicate that sustainability reporting, managerial ownership, and independent boards of commissioners have a significant influence on reducing earnings management practices. This demonstrates that ESG transparency and internal governance mechanisms are effective in aligning interests and strengthening oversight. Conversely, institutional ownership was found to have no significant effect on earnings management, indicating that the role of institutional investors in external oversight is not yet optimal in this sector. This research provides empirical evidence on the importance of strengthening governance structures and non-financial transparency as strategies to mitigate information asymmetry. For regulators and companies, these results emphasize the need for standardization of sustainability reporting to improve earnings quality and protect the integrity of the Indonesian capital market.